1999
DOI: 10.1159/000023436
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Binding Protein (IGFBP)-3-Bound IGF-I and IGFBP-3-Bound IGF-II in Growth Hormone Deficiency

Abstract: In blood, circulating IGFs are bound to six high-affinity IGFBPs, which modulate IGF delivery to target cells. Serum IGFs and IGFBP-3, the main carrier of IGFs, are upregulated by GH. The functional role of serum IGFBP-3-bound IGFs is not well understood, but they constitute the main reservoir of IGFs in the circulation. We have used an equation derived from the law of mass action to estimate serum IGFBP-3-bound IGF-I and IGFBP-3-bound IGF-II, as well as serum free IGF-I and free IGF-II, in 129 control childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…If affinity data from competitive solution affinity assays are used [5], considerably lower free IGF-I concentrations are found, as shown in table 2. Significantly lower calculated serum free IGF-I was also reported by Belgorosky and Rivarola [2] using affinity data from Bach et al [5] and taking all six IGFBPs as well as IGF-II into consideration. It is probable that the presence of excess ALS in serum, which is not taken into consideration here, results in even lower free IGF-I concentrations.…”
Section: Serum Free Igf-i Concentrations: Can They Be Calculated?mentioning
confidence: 57%
See 1 more Smart Citation
“…If affinity data from competitive solution affinity assays are used [5], considerably lower free IGF-I concentrations are found, as shown in table 2. Significantly lower calculated serum free IGF-I was also reported by Belgorosky and Rivarola [2] using affinity data from Bach et al [5] and taking all six IGFBPs as well as IGF-II into consideration. It is probable that the presence of excess ALS in serum, which is not taken into consideration here, results in even lower free IGF-I concentrations.…”
Section: Serum Free Igf-i Concentrations: Can They Be Calculated?mentioning
confidence: 57%
“…At equilibrium, the concentration of unbound reactant in a simple reaction between two reactants such as IGF and IGFBP can be calculated from the law of mass action by the equation: Although it may theoretically be possible to calculate the free IGF-I concentration in serum [2], the IGF system is highly complex. It consists of IGF-I and IGF-II, the high-affinity binding proteins-1 to -6, the ALS that forms ternary complexes with IGFs bound by either IGFBP-3 or -5, as well as IGFBP-related proteins with significantly lower affinities.…”
Section: Serum Free Igf-i Concentrations: Can They Be Calculated?mentioning
confidence: 99%
“…Intramuscular injection of the Lenti-IGF-1 vector rescued the serum IGF-1 deficiency and the elevated serum creatinine (Figure 2). We also evaluated the effects of IGF-1 + IGFBP3 because BP3 is the major IGF binding protein circulating in the blood [30]. However, we observed no superiority using the IGFBP3 in a survival study (data not shown), and therefore, we performed our studies with only in vivo IGF-1 gene therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Serum IGF-I was determined by RIA, after acid-ethanol extraction of serum, as previously reported 12 nostic kit (DSL); intra-assay and interassay CVs were 5.3-6.7% and 6.7-8.3%, respectively.…”
Section: Methodsmentioning
confidence: 99%